2021
DOI: 10.17533/udea.ikala.v26n01a07
|View full text |Cite
|
Sign up to set email alerts
|

Intermodality and Multilingual Re-instantiation: Joint Construction in Bilingual Genre Pedagogy

Abstract: This paper discusses the roles of intermodality and multilingualism in a genre pedagogy program aimed to improve students’ literacy in Indonesia. It draws on data from an intervention program which extended the Reading to Learn (R2L) genre-based literacy pedagogy to embed English literacy learning in biology lessons for Indonesian junior high school students. This bilingual R2L program is innovative in that it involves the use of written and spoken Bahasa Indonesia and English for both teaching materials and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Besides, in Malaysia (Singh, 2015) and China (Gang Li et al, 2010), the students experienced obstacles while practicing academic writing in an instructional setting where English has been applied as a medium language. A similar case is also exhibited by Indonesian students (Ariyanti & Fitriana, 2017;Ningsih, 2016;Yaqin, 2015). They faced grammatical difficulties, formulated the right coherence and cohesion, and developed the --------------------------------------------------------------------------------------------------------------------Volume 12 No 1, February 2023, http://creativecommons.org/licenses/by/4.0 95 ideas in their essay.…”
Section: Introductionsupporting
confidence: 53%
“…Besides, in Malaysia (Singh, 2015) and China (Gang Li et al, 2010), the students experienced obstacles while practicing academic writing in an instructional setting where English has been applied as a medium language. A similar case is also exhibited by Indonesian students (Ariyanti & Fitriana, 2017;Ningsih, 2016;Yaqin, 2015). They faced grammatical difficulties, formulated the right coherence and cohesion, and developed the --------------------------------------------------------------------------------------------------------------------Volume 12 No 1, February 2023, http://creativecommons.org/licenses/by/4.0 95 ideas in their essay.…”
Section: Introductionsupporting
confidence: 53%
“…Figure 2 shows how the pedagogical sequence P/V/R is incorporated into the R2L pedagogy. Other foreign-language bilingual adaptations of R2L include Kartika-Ningsih and Rose (2021) and Kartika-Ningsih (2016). In the frame of bilingual biology lessons at a junior high school in Indonesia, they extended R2L genre-based literacy pedagogy to embed written and spoken Indonesian and English for both teaching materials and instruction, especially for the Joint Construction strategy.…”
Section: Purposefully Utilizing L1 In Teaching L2 To Reduce Cognitive Overloadmentioning
confidence: 99%
“…Reading to Learn (R2L) pedagogy has gained much attention for its success in teaching writing for more than a decade (Kartika-Ningsih & Rose, 2021;Tardy et al, 2018;Wen et al, 2022;). It offers a pedagogical tool for teachers and students to examine the network of lexico-grammatical choices and use them in making meaning in their texts.…”
Section: Introductionmentioning
confidence: 99%
“…On this front, Rose and Martin (2012) argue that R2L pedagogy provides tools for teachers to support student participation so that all students have access to their success. Arguably, maximal support enables all students to participate actively and acquire knowledge of curriculum (Kartika-Ningsih & Rose, 2021). In their study, Fenwick and Herrington (2022) reported that teaching strategies from genre pedagogy such as preparing, focusing, and elaborating during text deconstruction, increased the number of students who participate in the classroom dialogue.…”
Section: Introductionmentioning
confidence: 99%